Parallel Multi-Gene Panel Testing for Diagnosis of Idiopathic Hypogonadotropic Hypogonadism/Kallmann Syndrome. (27th October 2019) - Senthilraja, Manickavasagam; Chapla, Aaron; Jebasingh, Felix K.; Naik, Dukhabhandhu; Paul, Thomas V.; Thomas, Nihal
Abstract : Kallmann syndrome (KS)/Idiopathic hypogonadotropic hypogonadism (IHH) is characterized by hypogonadotropic hypogonadism and anosmia or hyposmia due to the abnormal migration of olfactory and gonadotropin releasing hormone producing neurons. Multiple genes have been implicated in KS/IHH. Sequential testing of these genes utilising Sanger sequencing is time consuming and not cost effective. The introduction of parallel multigene panel sequencing of small gene panels for the identification of causative gene variants has been shown to be a robust tool in the clinical setting. Utilizing multiplex PCR for the four gene KS/IHH panel followed by NGS, we describe herewith two cases of hypogonadotropic hypogonadism with a Prokineticin receptor 2 (PROKR2) gene and KAL1 gene mutation. The subject with a PROKR2 mutation had a normal perception of smell and normal olfactory bulbs on imaging. The subject with a KAL1 gene mutation had anosmia and a hypoplastic olfactory bulb.